Mosquitoes - Miller, Connie Colwell, 1976- (Mankato, Minn. : Capstone Press, 2005)
A brief introduction to mosquitoes, discussing their characteristics, habitat, life cycle, and predators.
Includes bibliographical references and index.
Accelerated Reader AR
Keywords: Mosquitoes